German images of the self and the other : nationalist, colonialist and anti-semitic discourse 1871-1918 - Rash, Felicity J., 1954- (Palgrave Macmillan, 2012)
This monograph is a detailed linguistic analysis of the discourse of German nationalism, colonialism and Anti-Semitism using a methodological framework devised by Ruth Wodak et al., the Discourse Historical Approach. It pays particular attention to the discourse strategies, argumentation topoi and metaphors used by a selection of representative authors of both political propaganda and fiction. The study shows how the analysis of linguistic and social behaviour and the connection between them sheds light on the nature and effects of human behaviour, and on the motives and reasoning behind human actions. Within the context of nationalism and prejudiced behaviours, the construction in discourse of individual and group 'self-images' and the discursive means of contrasting these with 'other-images' is of major significance. It is widely believed that a self-image can only be formed if an image of a so-called "Other" exists as a focus of contrast and (frequently) suspicion and antipathy, which in extreme cases can lead to fear and hatred. Fear and hatred of the 'Other' in the form of racism and racial anti-Semitism, and the discursive representation of these, is therefore a major focus of this study